Strategies for a transition towards a solar district heating grid with integrated seasonal geothermal energy storage. (1st August 2021) - Formhals, Julian; Feike, Frederik; Hemmatabady, Hoofar; Welsch, Bastian; Sass, Ingo
Abstract: District heating plays a key role in achieving the TU Darmstadt's emission reduction target for 2050. A combination of efficiency measures, integration of solar thermal collectors, waste heat utilization and seasonal storage is being considered to achieve these targets. However, the existing campus building infrastructure does not allow for an efficient immediate transition to a low-temperature solar district heating grid. Therefore, a stepwise transition with a successive reduction of the grid temperatures is investigated. Dynamic system simulations serve to compare transition strategies until 2050 with regard to their environmental performance and economic efficiency. The proposed strategies differ in dimensions of components as well as the timing of construction or decommissioning. Results indicate that the emission reduction target can be met most economically by a strategy with a gradual construction of 42, 000 m 2 of solar thermal collectors and a seasonal storage consisting of 37 boreholes of 750 m each, accompanied by a concurrent scaling-down of the existing CHP capacity. Compared to a strategy with an immediate construction of a full-sized system, the levelized cost of heat can be reduced from 7.6 ct/kWh to 6.3 ct/kWh, as projected renovation rates, energy prices and emission factors are taken into account better. Highlights: Transition strategies towards a 4GDH grid are compared using dynamic simulations. A most economic strategy satisfying emission reduction targets is identified. Solar thermal collectors and a BTES should be integrated step-wise. Premature phase-out of CHP technology impairs transition costs. A gradual transition strategy can significantly reduce emission saving costs.